Flexible Piezoelectric Energy Harvesting from Mouse Click Motions - Youngsu Cha; Jin Hong; Jaemin Lee; Jung-Min Park; Keehoon Kim (Sensors, 2016)
In this paper, we study energy harvesting from the mouse click motions of a robot ﬁnger and a human index ﬁnger using a piezoelectric material. The feasibility of energy harvesting from mouse click motions is experimentally and theoretically assessed. The ﬁngers wear a glove with a pocket for including the piezoelectric material. We model the energy harvesting system through the inverse kinematic framework of parallel joints in a ﬁnger and the electromechanical coupling equations of the piezoelectric material. The model is validated through energy harvesting experiments in the robot and human ﬁngers with the systematically varying load resistance. We ﬁnd that energy harvesting is maximized at the matched load resistance to the impedance of the piezoelectric material, and the harvested energy level is tens of nJ.